Designing Reading Platform UIs and Standardizing Accessibility: A study of digital reading preferences across disability communities that impact the user experience for all readers (Journal of Accessibility and Design for All, 2025)
In an era where everyone will experience a disability at some point (even if temporary), inclusive design is increasingly vital to information accessibility for all users. This study aims to learn the digital reading preferences of various disability communities and address implications for a design for all approach to improve the digital reading experience for everyone. Method. Research questions systematically guided the exploratory review, resulting in 14 studies that underwent thematic analysis with inductive coding.  Results. With a lens from the information science, user experience, and disability studies fields, this paper presents five themes identified across the studies. Digital reading preferences of people with and without disabilities and recommendations for digital reading designs are discussed. Conclusion. Culture, assumptions, and misperceptions of accessibility, disability, technology, and literacy play a part in how society and social accessibility impact people with and without disabilities. This paper presents preliminary findings, gaps, and limitations that provide future steps for this project and other research directions. The viewpoint of disability communities may help increase the accessibility, usability, and enjoyment of digital reading more broadly, where design for all can be the tool for standardizing accessibility, which benefits everyone.